Voluntary Absolutism: British Missionary Societies in the Nineteenth Century - Hinchliff, Peter (Studies in church history, 1986)
In 1818 Dr John Philip was sent out to supervise the London Missionary Society stations at the Cape of Good Hope. His first letter to the Society’s headquarters is dated from Liverpool on 5 December of that year and contains the statement, ‘We have been at sea for seventeen days and are still in the Mersey River.’ Philip went on to ask for various items, including - significantly perhaps - a barometer! And there was time for the barometer to reach him before he left the Mersey: it was a further five days before the winds changed.